2014
DOI: 10.1097/tp.0b013e3182a68953
|View full text |Cite
|
Sign up to set email alerts
|

Living-Donor Liver Transplantation Associated With Higher Incidence of Hepatocellular Carcinoma Recurrence Than Deceased-Donor Liver Transplantation

Abstract: In conclusion, LDLT showed poorer outcome than DDLT. This should be considered to select optimal strategy for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 15 publications
1
59
0
1
Order By: Relevance
“…We also reported that LDLT showed worse outcomes than DDLT among patients within the UCSF criteria when having poor tumor biology (high AFP, microvascular invasion, high histological grade). This may be due to different clinical characteristics of LDLT such as a fast-track effect and graft regeneration (12). Based on these results, conventional criteria from DDLT based analysis, such as Milan criteria and UCSF criteria, focusing on tumor number and size are not similarly effective to stratify survival in LDLT.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We also reported that LDLT showed worse outcomes than DDLT among patients within the UCSF criteria when having poor tumor biology (high AFP, microvascular invasion, high histological grade). This may be due to different clinical characteristics of LDLT such as a fast-track effect and graft regeneration (12). Based on these results, conventional criteria from DDLT based analysis, such as Milan criteria and UCSF criteria, focusing on tumor number and size are not similarly effective to stratify survival in LDLT.…”
Section: Discussionmentioning
confidence: 94%
“…Dynamic liver CT or MRI, chest CT, and bone scan including serum tumor markers were checked every 3 to 6 months for the first one and a half year depending on the risk factors such as high AFP, microvascular invasion, and high histological grade, and every 6 months to 1 year thereafter (11,12). PET was also performed for patients with a high-risk of recurrence, such as patients who did not meet the Milan criteria, and patients with increasing tumor markers without abnormal liver function.…”
Section: Post-transplantation Management and Follow-upmentioning
confidence: 99%
“…Studies reporting a poorer outcome in the LDLT setting Park et al [10] recently reported poorer recurrence-free survival among 166 LDLT recipients (81% at 5 years) compared to 50 DDLT recipients (94% at 5 years; P = 0.045). The noteworthy finding of this study was that the smaller the LDLT graft, the poorer the recurrence -free survival.…”
Section: For Hcc Patientsmentioning
confidence: 99%
“…In 2014, Park et al (17) reported the results of 216 OLT recipients with HCC who met the UCSF criteria (166 LDLT and 50 DDLT). Recurrence-free survival was significantly lower with LDLT compared to DDLT (88.6% and 80.7% vs. 96.0% and 94.0% at 1-and 5-year, P=0.045).…”
Section: Recent Reportsmentioning
confidence: 99%
“…Therefore, LDLT for patients with HCC is being accepted worldwide as a solution to donor shortage and waiting list mortality (11,12). However, with the accumulation of cases, higher recurrence rates after LDLT in comparison to DDLT have been reported by several authors (13)(14)(15)(16)(17). In this review, we aim to present a current overview of the outcomes of LDLT compared to those of DDLT in patients with HCC, with emphasis on the recurrence of HCC.…”
Section: Introductionmentioning
confidence: 99%